PEDAGOGICAL COMPETENCE OF DRIVING TEACHERS ON STUDENTS WITH INTELLECTUAL DISABILITIES IN UNDERSTANDING DIGITAL LITERACY - Eunike, Pratiwi; Bintoro, Wahyu; Yuli, Wahyu; Wowor, Vrolly; Laia, Martin (QUAERENS: Journal of Theology and Christianity Studies, 2022)
Teachers are professional educators whose main tasks are to educate, teach, direct, train, assess and evaluate students based on Law No. 14/2005. These competencies apply to all educators including those who teach in special schools. Pedagogical competence of teachers in students with disabilities faces challenges as a driving teacher who continues to process, progressive and innovative and dynamic in the digitalization era for a comprehensive balance of human resources in the teaching and learning process. The purpose of this study is to describe the Pedagogical Competence of teachers as a driving force in overcoming the problems of intellectually retarded students in schools in understanding digital literacy in the learning process. The research method used is a qualitative field and literature method where the data is sourced from interviews, observations in the field and phenomena that exist around also collecting references from previous journals, books and literature that are in accordance with the discussion. All data sources are compiled to make a conclusion. The results of the study show a graphical increase in the intellectual development of students and being able to understand digital literacy when teachers innovate and use pedagogical competencies to the fullest to arouse students' interest in learning and hone their cognition so that they can understand digital literacy simply.